Evaluation of Sweet Potato Leaves and Cassava Leaves Inclusions into the Diet Containing Lemuru Oil on Lipid Metabolism in Local Duck - Nurrofingah, U.; Sumiati, Sumiati; Retnani, Y. (Tropical Animal Science Journal, 2020)
The objective of this study was to evaluate the effects of sweet-potato leaves and cassava leaves inclusions into the diet containing lemuru oil on lipid metabolism of local laying ducks. One hundred and eighty laying ducks with an average body weight of 1657 g were divided into 6 groups of experimental diets with 3 replications and 10 ducks in each replication. The experiment was arranged in a 2 x 3 factorial design. The first factor was the level of sweet potato leaves consisted of 2 levels, i.e., 0% and 5%. The second factor was the level of cassava leaves consisted of 3 levels, i.e., 0%, 5%, and 10%. The variables observed were performance of laying duck, blood, meat, and egg lipid profile, as well as the relationship between the average consumption of β-carotene with cholesterol concentration in the blood, egg, and meat of laying duck. The results showed that there was no interaction and no effect between sweet potato leaf meal (SPLM) and cassava leaf meal (CLM) on feed consumption. Different levels of SPLM and CLM gave a significant interaction effect (p